Neutrino astronomy: current status, future prospects/ Thomas K Gaisser, Albrecht Karle eds. - Gaisser, Thomas; Karle, Albrecht (New Jersey: World Scientific, 2017)
This review volume is motivated by the recent discovery of high-energy astrophysical neutrinos by IceCube. The aim of the book is to bring together chapters on the status of current and future neutrino observatories with chapters on the implications and possible interpretations of the present observations and their upper limits. Each chapter is a mini-review of one aspect of the subject by leading experts. Taken together, the chapters constitute an up-to-date review of high-energy astrophysical neutrinos and their potential sources. © 2017 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Gamma-Ray Bursts as Neutrino Sopurces -- Active Galactic Nuclei as High-Energy Neutrino Sources -- The Origin of IceCube's Neutrinos: Cosmic Ray Accelerators Embedded in Star Forming Calorimeters.-- Galactic Neutrino Sources -- Observations of Diffuse Fluxes of Cosmic Neutrinos -- IceCube and Asrtrophysical Neutrinos: The Search for Sources -- recent results from the ANTARES Neutrino Telescope -- The Baikal Neutrino Project -- The Dawn of Multi-messenger Astronomy -- Neutrino from Core-Collapse Supernovae -- The Quest for Dark Matter with Neutrino Telescopes -- KM3NeT: Astroparticle and Oscillations Research with Cosmic in the Abyss -- A next-generation IceCube: the Ice Cube-Gen2 Facility for High Energy Neutrino Astronomy -- Neutrino Physics with very Large Volumn Neutrino Telescopes -- Radio Detection of High Energy Neutrinos
Includes bibliographical references and index
Keywords: Physics; Astrophysics